Analysis of Combustion Temperature on Specific Fuel Consumption (SFC) of Diesel Engines Using B100 and B20 Fuel in the Long Term - Wiliandi Saputro; Muhammad Ikhsan; Erwan Adi Saputro; Wahyu Dwi Lestari; Luluk Edahwati; Ahmad Khairul Faizin; Sutiyono; Ndaru Adyono; Tria Puspa Sari; Radissa Dzaky Issafira (Nusantara Science and Technology Proceedings, 2022)
Indonesia is one of the largest palm oil-producing countries globally, with a production value of 40 million tons by 2020. Biodiesel is one of the alternative energy sources that can be processed from palm oil. Diesel engines can directly use biodiesel as a fuel. Biodiesel has distinct characteristics from diesel; thus, it will affect performance and other things on the engine. In this research, diesel engine performance tests were carried out, including specific fuel consumption (SFC), cylinder head temperature, cylinder block, and exhaust pipe, with a test time of 300 hours. This research aims to determine the effect of the cylinder head, cylinder block, and exhaust pipe temperatures on SFC using two different fuels, i.e., B100 and B20. Based on the test results, the average cylinder head, cylinder block, and exhaust pipe temperatures on the B100 engine are 136 oC, 130 oC, and 257 oC. As for the B20 engine's cylinder head, block, and exhaust pipe temperatures are 139 oC, 132 oC, and 264 oC. Engine with B100 fuel obtained SFC of 0.317 kg/kW.hour and engine with B20 fuel obtained SFC of 0.276 kg/kW.hour. In general, the combustion temperature in the cylinder head affects the increase in SFC in both engines with different fuels; the higher the combustion temperature in the cylinder head, the higher the SFC is. Engines with B100 fuel have a higher SFC value than B20 fuel, which is influenced by the higher viscosity and density values; thus, the droplets from the fuel atomization process become larger when compared to fuels with lower viscosity and density values. The graph analysis shows that the cylinder block temperature graph on the B100 and B20 fueled engines decreases between temperatures of 133-134 oC, then inflates with the increase in specific fuel consumption. The higher temperature compared to the B100 fuel engine makes the fuel undergo complete combustion when injected into the combustion chamber due to atomization or very fine droplets burning completely. The cylinder block temperature chart on the B100 and B20 fueled engines has a very significant trend difference. B100 engines tend to experience a decreasing trend in temperature along with an increase in SFC, while B20 engines tend to experience an increasing temperature trend along with an increase in SFC.